Comparative evaluation of soil physico-chemical properties under rubber, teak, sal and gamair plantation in south Tripura - Choudhuri M; Chaudhari D; Dey S K; Sarma A C (Placrosym XVII, 2006, Kochi, India. Journal of Plantation Crops, 34 (3). Indian Cardamom Research Institute (Spices Board), Idukki, India, pp.347-351.)
Physico-chemical properties of soil under different plantations and surrounding fallow land in South Tripura were compared in the study. Soil was acidic in nature. The soil texture was sandy clay loam in all the sites and coarser fragments dominated the soil separates. Organic carbon content and available nutrients were significantly higher under plantations compaerd to fallow land. Organic carbon content (1.00;) and availabel potassium were (5.08 mg/100g) highest under rubber in the surface layer (0-30 cm). Available phosphorus was highest under sal (1.09 mg/100g) in the surface layer. Vertical reduction in available nutrients was observed in all the sites. CEC of soil ranged from 8.62 to 13.39 Cmol (p+)/kg in the surface layer and it was highest under sal. The CEC per unit clay did not show appreciable difference among the sites. The percent base saturation of the soil ranged from 56.01 to 65.90 in the surface layer and 51.36 to 61.96 in the sub surface layer. Ca and Mg dominated the exchange complex followed by K and Na. The divalent: monovalent cations ratios ranged from 6.73-16.00 in the surface layer and 8.25-20.33 in the subsurface layer. The Ga:Mg rations ranged from 1.70 to 2.33 in the surface soil and 1.80 to 3.25 in the subsurface soil.
Keywords: Available nutrients; Soil physico-chemical properties; Tripura